2023
DOI: 10.59865/abacj.2024.1
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Relationship between Cryptocurrencies and Other Major World Economic Assets: A Granger Causality Test

Umawadee Detthamrong,
Seksak Prabpala,
Akkharawoot Takhom
et al.

Abstract: This study examines the causal relationship between cryptocurrencies and other major world economic assets, such as gold, stocks, oil, and bonds, using both Granger causality and correlation analyses. The study focuses on the period between 2018 and 2022, using a vector autoregressive model (VAR) to analyze data on cryptocurrencies and other major world economic assets, which collectively represent over 90% of the market during the observed period. Results show that correlation clearly identifies causal interd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It was found that GB and CE sources respond to shocks at low and high time frame frequencies, but the global environment and sustainability index distributes shocks to other indices at low and high time frame frequencies. Moreover, the level of interconnectedness varies over time and depends on economic events [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was found that GB and CE sources respond to shocks at low and high time frame frequencies, but the global environment and sustainability index distributes shocks to other indices at low and high time frame frequencies. Moreover, the level of interconnectedness varies over time and depends on economic events [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a different area of business, the seventh article relates to cryptocurrencies and the financial market. Detthamrong et al (2024) examines the causal relationship between cryptocurrencies and other major world economic assets, such as gold, stocks, oil, and bonds, using Granger causality and correlation analyses during 2018-2022 (represent over 90% of the market during the observed period). The results reveal that there is Granger causality between the cryptocurrencies (Tether, USD Coin, and Binance USD) and the other major world economic assets (BOND, SP500, and GOLD).…”
Section: Articles In This Current Issuementioning
confidence: 99%